2(x²-6)=3(x-4) solve it using factorisation
Answers
Answered by
7
Answer:
Step-by-step explanation:
hope it helps you....
plz mark me as brainleast plz plz....
also follow me plz...
Attachments:
![](https://hi-static.z-dn.net/files/d3a/abe30cf3cf1fead9342ed93b253ddd83.jpg)
Answered by
3
☆ To Solve:-
- 2(x²-6) = 3(x-4).
☆ Now,
=》 2x²-12 = 3x-12.
{Opening Brackets}
=》 2x²-12-3x+12 = 0.
=》 2x²-3x-12+12 = 0.
=》 2x²-3x = 0.
=》 2x²-3x = 0.
=》 x(2x-3) = 0.
Therefore Either x = 0 or 2x-3 = 0
Or,
Hope this will help you if it HELPS then plz mark my answer as BRAINLIEST:D
And remember to always keep a smile on face:D
Similar questions